Agric Financing and its Impact on Agricultural GDP: An ARDL Approach - Victor C, Ndubuaku; E.U, Okoro Okoro; Kabiru, Bello; Chiaka P, Alozie (International Journal of Sustainable Agricultural Research, 2019)
This research investigated the impact of agricultural financing on agricultural sector contribution to GDP in Nigeria. The objective of the study was to determine whether agricultural financing had any significant impact on agricultural contribution to GDP in Nigeria. The dataset covered a 36year period from 1981-2016. Data was sourced from the CBN statistical Bulletin. The dependent variable was the Agricultural GDP (AGDP). The independent variables were government funding {represented by Government Capital Expenditure on Agriculture (GCAG) and Government Recurrent Expenditure on Agriculture (GRAG) }, Agric Credit Guarantee scheme Fund (ACGSF) and Commercial Banks’ Credit, Loans and Advances to the Agricultural Sector (CBCA). Standard analytical tests were used to determine the properties of the data. The Auto Regressive Distributed Lagged regression model (ARDL) was used to estimate the data. The study found that government funding to agriculture and Agric Credit Guarantee scheme Fund (ACGSF) had a non-significant impact on Agricultural Contribution to GDP (AGDP). On the other hand, the study found that Commercial Banks’ Credit, Loans and Advances to the Agricultural Sector (CBCA) had a positively significant impact on AGDP. The study recommended the sustenance of government policy that encouraged consistent injection of funds into agriculture. It advocated that a sizeable portion of Commercial Banks’ credit should be channelled to agricultural production.